Impurity in a heteronuclear two-component Bose mixture - Bighin, Giacomo; Burchianti, A.; Minardi, F.; Macrì, T. (Physical review, 2022)
We study the fate of an impurity in an ultracold heteronuclear Bose mixture, focusing on the experimentally relevant case of a 41K−87Rb mixture, with the impurity in a 41K hyperfine state. Our paper provides a comprehensive description of an impurity in a BEC mixture with contact interactions across its phase diagram. We present results for the miscible and immiscible regimes, as well as for the impurity in a self-bound quantum droplet. Here, varying the interactions, we find exotic states where the impurity localizes either at the center or at the surface of the droplet.
Gesehen am 13.03.2023